Descartes y More: Materia vs Espíritu.Un debate sobre el espacio en el siglo XVII - Caviglia Marconi, Alessandro (2026)
This article examines Henry More’s criticism of René Descartes in the 17th century regarding the nature of space. The central problem lies in the inadequacy that More identifies in the Cartesian mechanistic conception, particularly in its reduction of space to mere corporeal extension. In response, the aim of the text is to show how More proposes a more complex distinction between corporeal substance and spiritual substance, which allows him to expand the limits of mechanism and question the ability of the Cartesian model to explain phenomena related to action, presence, and spiritual causality. From this framework, the main terms of the debate are reconstructed in order to clarify both Descartes’ position and More’s critical response. This reconstruction allows us to reflect on the metaphysical implications of upholding a concept of space that exceeds pure materiality and opens up the possibility of a world structured by principles that cannot be reduced to the physical. Finally, the article argues that More’s objections not only illuminate internal tensions within Cartesianism, but also allow us to appreciate the originality of his thinking in the early configuration of a philosophy that seeks to integrate the spiritual into the understanding of the world.